1990
DOI: 10.1007/bf01316307
|View full text |Cite
|
Sign up to set email alerts
|

Diets of piscivorous fishes in a tropical Australian estuary, with special reference to predation on penaeid prawns

Abstract: Abstract. The diets of fish from the tropical Embley Estuary in the eastern Gulf of Carpentaria, Australia, were analysed with particular reference to piscivory and predation on juveniles of commercially important penaeid prawns from October 1986 until July 1988. Of the 77 species caught, 52 were piscivorous, and of these 37 ate penaeid prawns. The most numerous piscivores were Scomberoides commersonianus, Arius proximus, Lates calcarifer, Polydactylus sheridani and Rhizoprionodon acutus, the first four of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 23 publications
8
78
1
1
Order By: Relevance
“…A concentration by platycephalids on a few types of crustaceans, such as carid decapods (Humphries et al, 1992) or crabs (Klumpp & Nichols, 1983), often reflects a local abundance of these respective prey types. Since epibenthic mysids make a greater contribution to the diet of P. longispinis in this study than has been recorded for other platycephalids (see Klumpp & Nichols, 1983;Marais, 1984;Salini et al, 1990;Humphries et al, 1992) and are also an important component of the diets of several other fish species in the study area ; M.E.P., unpublished data), they are presumably very abundant in the inner shelf waters of south-western Australia. Platycephalus longispinis also ingested a considerable volume of small demersal teleost species, such as gerreids, which are very abundant locally .…”
Section: Dietary Compositionmentioning
confidence: 91%
See 1 more Smart Citation
“…A concentration by platycephalids on a few types of crustaceans, such as carid decapods (Humphries et al, 1992) or crabs (Klumpp & Nichols, 1983), often reflects a local abundance of these respective prey types. Since epibenthic mysids make a greater contribution to the diet of P. longispinis in this study than has been recorded for other platycephalids (see Klumpp & Nichols, 1983;Marais, 1984;Salini et al, 1990;Humphries et al, 1992) and are also an important component of the diets of several other fish species in the study area ; M.E.P., unpublished data), they are presumably very abundant in the inner shelf waters of south-western Australia. Platycephalus longispinis also ingested a considerable volume of small demersal teleost species, such as gerreids, which are very abundant locally .…”
Section: Dietary Compositionmentioning
confidence: 91%
“…Platycephalus longispinis also ingested a considerable volume of small demersal teleost species, such as gerreids, which are very abundant locally . Other platycephalid species have also been found to consume teleosts to a similar or greater extent (Colefax, 1938;Marais, 1984;Salini et al, 1990;Humphries et al, 1992).…”
Section: Dietary Compositionmentioning
confidence: 99%
“…All 3 species of prawns are eaten by several species of fish in the Embley River (Salini et al 1990). Although some of the fish feed at night, many feed primarily in the day and so decreased prawn activity during the day would probably decrease the chances of predation by fish and birds.…”
Section: Activity Patterns and Habitatmentioning
confidence: 99%
“…Whilst the impact of fish predation on adult penaeids has been well studied (Pauly and Palomares, 1987;Salini et al, 1990;Sheridan et al, 1984), predation rates on juveniles in estuaries and coastal waters have received less attention. This is possibly because postlarval and juvenile penaeids are rapidly digested in fish stomachs, causing them to be underrepresented in stomach content analyses; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Salini et al (1990) found that 37 of the 77 fish species collected in the Embley Estuary fed on juvenile penaeids, which were a significant component of the diets of three of the most abundant predators. Numerous studies have found that many predatory fish are size selective; i.e.…”
Section: Introductionmentioning
confidence: 99%